Phosphorous Efficiency and Tolerance Traits for Selection of Sorghum for Performance in Phosphorous‐Limited Environments. Issue 3 (1st May 2015) - Leiser, Willmar L.; Rattunde, H. Frederick W.; Piepho, Hans‐Peter; Weltzien, Eva; Diallo, Abdoulaye; Toure, Abocar; Haussmann, Bettina I.G.
ABSTRACT: Sorghum ( Sorghum bicolor (L.) Moench) is widely cultivated in West Africa (WA) on soils with low phosphorus (P) availability. Large genetic variation for grain yield (GY) under low‐P conditions was observed among WA sorghum genotypes, but information is lacking on the usefulness of P‐tolerance ratios (relative performance in –P [no P fertilizer] vs. +P [with P fertilizer] conditions) and measures of P‐acquisition and internal P‐use efficiency as selection criteria for enhancing GY under low‐P conditions. We evaluated 70 WA sorghum genotypes for GY performance under −P and +P conditions for 5 yr in two locations in Mali and assessed P acquisition (e.g., P content in biomass) and P‐use efficiency (e.g., grain produced per unit P uptake) traits under −P and +P conditions in one site in 2010. Significant genetic variation existed for all P‐tolerance ratios across multiple sites. Photoperiod‐sensitive landrace genotypes showed significantly better P tolerance and less delay of heading under P‐limited conditions compared with photoperiod‐insensitive varieties. Genotypic correlations of P‐tolerance ratios to GY under −P were moderate. Phosphorous acquisition and P‐use efficiency traits independent of harvest index were of similar importance for GY under −P conditions in statistically independent trials. However grain‐P and stover‐P concentrations from one −P trial showed only weak correlations with GYs in statistically independent trials. Highest predicted gains for −P GY were obtained by theoretical index selection based on −P GY combined with P‐use efficiency traits (e.g., low‐grain P concentration). Such index selection is expected to achieve both increased sorghum productivity and P sustainability in the P‐limited WA production systems.